2020
DOI: 10.1093/jrr/rrz086
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy evaluation of 2D, 3D U-Net semantic segmentation and atlas-based segmentation of normal lungs excluding the trachea and main bronchi

Abstract: This study aimed to examine the efficacy of semantic segmentation implemented by deep learning and to confirm whether this method is more effective than a commercially dominant auto-segmentation tool with regards to delineating normal lung excluding the trachea and main bronchi. A total of 232 non-small-cell lung cancer cases were examined. The computed tomography (CT) images of these cases were converted from Digital Imaging and Communications in Medicine (DICOM) Radiation Therapy (RT) formats to arrays of 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…Brain DWI often are highly anisotropic images since the slice thickness (i.e., z-axis) generally is much more than the in-plane spatial resolution (i.e., y and x-axes). Additionally, 3D U-net requires higher memory capacity, and it might require lowering the original spatial resolution or using patch-based approaches in the network, which inevitably leads to loss of contextual information 32 , 33 . Nevertheless, head-to-head comparisons of 3D U-net and ConvLSTM U-net in segmenting stroke lesions on DWI should be systematically explored in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Brain DWI often are highly anisotropic images since the slice thickness (i.e., z-axis) generally is much more than the in-plane spatial resolution (i.e., y and x-axes). Additionally, 3D U-net requires higher memory capacity, and it might require lowering the original spatial resolution or using patch-based approaches in the network, which inevitably leads to loss of contextual information 32 , 33 . Nevertheless, head-to-head comparisons of 3D U-net and ConvLSTM U-net in segmenting stroke lesions on DWI should be systematically explored in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Balagopal et al reported a DSC of 0.87 by a 2-D U-Net and 0.89 by a 3-D U-Net for prostate segmentation on CT images [18]. For segmentation of normal lungs, Nemoto et al reported no significant difference in the DSC between the 2-D and 3-D U-Nets [34]. The 3-D U-Net requires a fixed craniocaudal length for the input images, and in this study it was difficult to automatically select a uniform length because the craniocaudal organ lengths were variable.…”
Section: Discussionmentioning
confidence: 99%
“…Automated lung segmentation A deep learning approach based on the U-Net framework [16][17][18] was developed to ensure the automated segmentation of the lung boundary when there is pneumonia or consolidation adjacent to the chest wall. It is well-known that deep learning approaches are datahungry.…”
Section: B the Computerized Schemementioning
confidence: 99%